Strategi Pembelajaran Problem Based Learning di Perguruan Tinggi Islam pada Mata Kuliah Fiqh - Qutub, Sayid (SAP (Susunan Artikel Pendidikan), 2024)
The aim of this research is to determine the use of problem-based learning (PBL) learning strategies in learning fiqh courses at Islamic universities. The learning strategy Problem-based learning is considered as a learning strategy that can help students solve problems, strengthen their understanding of concepts, and improve spiritual aspects of religious learning. This research was conducted qualitatively using a descriptive analysis approach. In other words, the aim of this research is to describe an event based on interrelated facts and information. The research results show that the use of problem-based learning strategies can increase students' understanding of fiqh and encourage them to participate actively in solving problems related to everyday life. In addition, this model shows the potential to increase students' social awareness, integrity, and religious responsibility.